Удосконалення біотехнології анаеробної ферментації курячого посліду зі зниженою кількістю стоків - Шаповалов, Євгеній Борисович (НУБіП України, 2019)
Дисертація на здобуття наукового ступеня кандидата технічних наук зі спеціальності 03.00.20 «Біотехнологія». Національний університет біоресурсів і природокористування України. Київ, 2019. Дисертацію присвячено дослідженню підходів до зниження кількості утворення стоків у процесі анаеробної ферментації курячого посліду. Проведено дослідження стабільності анаеробної ферментації у твердофазних умовах і запропоновано підхід до інтенсифікації процесу. Досліджено анаеробну ферментацію курячого посліду за умови рециркуляції рідкої фази з вилученням амонійного Нітрогену. Здійснено економічну оцінку обох підходів та обґрунтовано вищу економічну ефективність за використання рідиннофазної ферментації з рециркуляцією рідкої фази. Запропоновано новий метод відновлення сорбенту для вилучення амонійного Нітрогену, що передбачає економічно привабливий метод виробництва амоніаку. Розроблено біотехнологію анаеробної ферментації курячого посліду за умови рециркуляції рідкої фази, що характеризується значимим зниженням кількості стоків
The thesis for scientific degree of candidate of technical sciences in specialty 03.00.20 «Biotechnology». National University of Life and Environmental Sciences of Ukraine. Kyiv, 2019. The dissertation is devoted to the study of approaches to reducing the amount of wastewater formation in the process of chicken manure anaerobic digestion. It has been proved that dry anaerobic digestion of chicken manure is characterized by low stability due to high concentrations of ammonium Nitrogen and hydrogen sulfide. The coefficient of variation of methane production ranged from 14.84 to 35.17 % in the mesophilic conditions and from 14.4 to 78.21 % in the thermophilic conditions. The highest coefficient of variation is characteristic of humidity of 78 % in thermophilic conditions, which is due to the presence of anaerobic fermentation inhibiting factors. It is worth noting that the moisture content had a much greater effect on the stability of the process in thermophilic mode than in mesophilic mode. Co-fermentation of chicken manure with glycerol after biodiesel production in concentrations of 10 %, 20, 30 % is characterized by decreasing the process efficiency. Biogas and methane production was observed only in case of 10 % addition of glycerol and it was decreased. During the anaerobic digestion process with addition 20 and 30 % of glycerol, biogas production wasn't observed at all. It may be due to that glycerol can contain alkali and methanol residues. Given that both mesophilic and thermophilic co-fermentation of chicken manure with biodiesel waste reduced the efficiency of anaerobic fermentation wasn't determined at all. Due that co-fermentation of chicken manure inhibition is caused by factors other than ammonium, it is appropriate to note that inhibition as a fact manifests itself much more strongly in thermophilic mode than in mesophilic ones. A more promising effect to intensify the dry anaerobic digestion of chicken manure is clay additions. The bentonite clay is characterized by better efficiency of ammonium sorption than agrellite clay. The addition of 25 % of red bentonite clay with an iron content of 15 % leads to decreasing of inhibition by both, ammonia and sulfides. The addition of bentonite clay allows for greater process stability. A close correlation between the content of red bentonite clay and the concentration of ammonium and hydrogen sulfide was established. During liquid anaerobic digestion of chicken manure with liquid phase recycling, it is proved the possibility of process intensification by sorption of ammonia using phosphoric acid located in the bioreactor. Therefore, biogas production in the control reactor varied from 0.044 to 0.83 l/(l·day) and 0.11 to 1.1 l/(l·day) in control bioreactor and bioreactor with ammonia reduction, respectively. The methane content in biogas from the bioreactor with ammonia sortition is significantly higher than in control bioreactor and it variated from 70 to 90 %. It is found that ammonia sorption leads to pH, conductivity, ammonium content, free ammonium content, and ammonia content in gas phase decreasing. The content of free ammonia during the seventh retention in the control reactor ranged from 1986.6 to 2510.8 mg/l, and in the experimental from 919.6 to 1445.4 mg/l. The average concentration of free ammonia during the seventh retention in the control reactor was 2136.8 mg/l and in the experimental 1285.7 mg/l. It means, that the efficiency of free ammonia content decreasing was 40 %. The process inhibition in the control bioreactor was much more intense than in the experimental one and is the explanation for the significant difference in biogas production. To find the quantity of recycled effluent during which ammonia content will not be higher than inhibition level (3 g/l), the mathematical modeling of sorption process was provided for recycled effluent quantity of 10–60 %, for the pH levels of 7.5, 8.0 and 8.5 and hydraulic retention time of 5 and 10 days. It is found that a safe continent of ammonia can be obtained during using 40 % of effluent recycling in case of pH 8.0 and hydraulic retention time of 10 days. The degree ammonium extraction can be significantly increased by changing the geometric dimensions of the biogas plant, increasing the contact area of the sorbent with the gas phase and the hydraulic retention time. It is proved that more economically effectively for minimization of more wastewater quantity is the technology of effluent recycling during liquid anaerobic digestion of chicken manure witch payback period of 1.25 years compared to more than 3 years during dry anaerobic fermentation with clay addition. It proved the efficiency of catalysis proving to decrease the volume of effluent and stop permanent biological activity during its storage. In addition, catalytical pyrolysis increases quality of the fertilizers by increasing the humate content which led to its coast increasing. It is proved, that obtained by catalytical pyrolysis fertilizer is characterized by high content of humates and will be useful for agriculture. The technology of sorbent regeneration which can provide its recycling without the nasality of additional sorbent purchasing costs is designed. The technology provides low-cost ammonia production which can be used as a single product or as fuel in ammonia fuel cells. The research results show that intensive process of the sorbent regeneration begins at the temperature of 80 °С. However, choosing the temperature modes will depend on the installation used produced ammonia. It is proposed to increase the sorbent area to provide increasing of the efficiency of ammonia sorption. Biogas reactor with huger sorbent area was developed. It differs from the previously proposed reactor by the increasing of the sorption tanks number. Anaerobic digestion biotechnology of chicken manure utilizing effluent recycling is characterized by the lower quantity produced wastewater and by high economical attractiveness witch 1.25 years of payback period and annually profit 60142 thousand UAH when using poultry farms with the 750 thousand of laying hens
Keywords: курячий послід; біотрансформація; анаеробна ферментація; стоки; амонійний Нітроген; chicken manure; biotransformation; anaerobic digestion; effluent; ammonium